Physics of the outer heliosphere : proceedings of the 1st COSPAR Colloquium held in Warsaw, Poland, 19-22 September 1989 - Grzedzielski, S.; Page, D. Edgar (COSPAR colloquia series, 1990)
This is the first volume in the new COSPAR Colloquia series which will provide a forum for an in-depth discussion on selective topics of importance to the international community. The International Heliospheric Study (IHS) was initially approved by COSPAR in 1982 when it was anticipated that the study would centre on the ESA/NASA Ulysses spacecraft. This mission was delayed until October 1990, but it was decided to commence the study in 1986 in order to exploit the existence of the Pioneer 10 and 11 and the Voyager 1 and 2 spacecraft in the outer heliosphere. The primary purpose of Physics of.